Worker health and safety and climate change in the Americas: issues and research needs - Max Kiefer; Julietta Rodríguez-Guzmán; Joanna Watson; Berna van Wendel de Joode; Donna Mergler; Agnes Soares da Silva
SYNOPSIS This report summarizes and discusses current knowledge on the impact that climate change can have on occupational safety and health (OSH), with a particular focus on the Americas. Worker safety and health issues are presented on topics related to specific stressors (e.g., temperature extremes), climate associated impacts (e.g., ice melt in the Arctic), and a health condition associated with climate change (chronic kidney disease of non-traditional etiology). The article discusses research needs, including hazards, surveillance, and risk assessment activities to better characterize and understand how OSH may be associated with climate change events. Also discussed are the actions that OSH professionals can take to ensure worker health and safety in the face of climate change.